2019
DOI: 10.1093/neuonc/noz038
|View full text |Cite
|
Sign up to set email alerts
|

The novel chromatin architectural regulator SND1 promotes glioma proliferation and invasion and predicts the prognosis of patients

Abstract: Background. Upregulation of staphylococcal nuclease domain-containing protein 1 (SND1) is a common phenomenon in different human malignant tissues. However, little information is available on the underlying mechanisms through which SND1 affects glioma cell proliferation and invasion. Methods. SND1, Ras homolog family member A (RhoA), and marker of proliferation Ki-67 (MKI67) were analyzed in 187 gliomas by immunostaining. The correlation between those markers and patients' prognoses was assessed using the Kapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Nonetheless, the clear alteration of these spliceosome components found in our global cohort of NFPTs has also been observed in other tumor pathologies. Specifically, SRSF9 and SND1 have been found overexpressed in several tumor pathologies, such as breast cancer, bladder cancer, glioblastoma, melanoma, or hepatocellular carcinoma, where they have been associated with an increase in cell proliferation, invasion and poor prognosis [47,48,49,50,51]. The fact that these SFs were downregulated in NFPTs, in contrast with the overexpression observed in other pathologies, may be likely reflect the complexity, heterogeneity, and limited functional deployment of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the clear alteration of these spliceosome components found in our global cohort of NFPTs has also been observed in other tumor pathologies. Specifically, SRSF9 and SND1 have been found overexpressed in several tumor pathologies, such as breast cancer, bladder cancer, glioblastoma, melanoma, or hepatocellular carcinoma, where they have been associated with an increase in cell proliferation, invasion and poor prognosis [47,48,49,50,51]. The fact that these SFs were downregulated in NFPTs, in contrast with the overexpression observed in other pathologies, may be likely reflect the complexity, heterogeneity, and limited functional deployment of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that SND1 overexpression promotes growth and metastasis of glioma cells. 35 Besides, other works also indicated that SND1 upregulation contributes to tumorigenesis, such as osteosarcoma, hepatocellular carcinoma and breast cancer. [36][37][38] Our data indicated that SND1 expression was upregulated in PC tissues.…”
Section: Dovepressmentioning
confidence: 99%
“…Breast cancer samples with phosphorylated RhoA (P-RhoA) were associated with poorer prognosis [27]. Lin Yu demonstrated that SND1 (Staphylococcal nuclease domain-containing protein 1) and RhoA were independent predictors of poor prognosis in glioma patients [28]. Our results suggested only a relationship between gender and RhoA gene expression.…”
Section: Discussionmentioning
confidence: 72%